Role of Cartographic Products in the Promotion of Tourism Based on the Example of Roztocze - Krzysztof Kałamucki; Andrzej Czerny (Barometr Regionalny, 2015)
The technologies of development, issuing, and visualisation of maps have changed over recent years. New forms of presentation have developed. Making maps available on mobile devices considerably increases their range of users. This can be used in a broadly defined scheme of promotion. This is determined in part by the practical function of maps, the mass and common character of their use, visualisation of maps on various information carriers, as well as the multimedial and interactive character of modern electronic maps. The objective of the article is to evidence the usefulness of modern cartographic products for the promotion of tourism. The issue will be presented based on the changing functions of modern maps, and based on the example of Roztocze. Maps evoke tourists’ interest in a tourist region. They show its special values and attractions, effectively encourage visits and exploration of the region, and create its positive image. The effect of maps on their recipients is strong due to the presentation of promotional content with the application of modern forms of cartographic communication. Owing to varied cartographic products, Roztocze is promoted both in the virtual (internet) and actual space (on information boards in the field). Abundantly issued tourist maps are available throughout the country, and complement the means of promotion of tourism in the region.